Valley Forge - Ammon, Richard (Holiday House, Scholastic, Inc, 2004)
Presents an illustrated account of the beginnings of the Revolutionary War, and tells the story of how George Washington transformed his army of ordinary citizens into an unbeatable fighting force over the course of a difficult winter at Valley Forge.